EFEK PEMASANGAN ISOLATOR TERHADAP KONSUMSI BAHAN BAKAR LPG MESIN SANGRAI BIJI KOPI INDUSTRI KECIL - Muhammad Trifiananto; Intan Hardiatama (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
Coffee beans in Jember Regency continue to be increased in line with the expansion of new crop fields. New coffee plantations plus 9 hectares were based on data from the Jember Regency Statistics Agency from 2008. Coffee bean production in Jember District in 2011 totaled 28,961.79 quintals, from 22,080.47 quintals for 2010. (Budiharjo, 2014). The increase in coffee bean production and land area is not followed by the level of prosperity of coffee farmers who own the land (Budiharjo, 2014). An appropriate technology to increase the selling value of coffee products  are roasting and packaging. The roasting method used greatly affects the quality of coffee. This study focused on the variation of insulators applied to roasting machines. The purpose of this study was to determine the rate of heat loss from the coffee roaster machine after being given the addition of an insulator and find out how much coffee production costs using a roaster machine which was given the addition of an insulator. Experimental research using a coffee roaster machine with LPG fuel with a capacity of 10 kg. Research was carried out by varying the insulators used such as without insulators, adding aluminum foil, adding glass wool, adding wood powder, adding glass wool and extruded polystrene foam, the last addition wood powder and extruded polystrene foam. Data retrieval was carried out using a temperature sensor and data logger with four thermocouple types K mak 6675. In addition to data retrieval of temperature, LPG consumption data was also collected. The results showed that the smaller thermal conductivity of an insulating material, produced lower  heat ratio and  lower  fuel consumption.